Acute effects of whole-body vibration on sprint running kinematics in sprint athletes - Gerakaki, M.; Paradisis, G.; Tziortzis, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Whole-body vibration (WBV) is a neuromuscular training method and has been promoted as an alternative or additional strength training method. The focus of many investigations was to determine the acute impact of a bout of whole-body vibration on athletic performance and the concerning parameters. Additionally, acute exposure to WBV, has been shown to induce transient increases in strength and power (Bosco et al, 1999) and has been suggested as a mode of warming up before practice, training and competition activities of athletes (Bazett-Jones et al., 2008). The aim of this study was to investigate the acute effects of WBV on sprint running kinematics in sprint athletes. The main hypothesis was that a single session of WBV would cause neuromuscular enhancement and improvement on sprint performance. Methods: The participants were 35 sprint athletes (21.9 ± 4.3 yrs, 176.7 ± 5.1 cm, 72.3 ± 7.5 kg) (personal 100m best time: 11.00 - 11.50 s, training experience > 3 yrs). The participants were randomly assigned into the experimental (E - with vibration) and control (C - without vibration) group. Both groups performed a single session of WBV consisted of two dynamic exercises (half squat / lunge) for total duration time of 90 s (Power Plate platform - 50Hz, 2mm). Sprint performance tests were performed from both groups, before (pre) and after (post) the WBV session and measured during a 60 m sprint. The time and average velocity at distances of 10, 20, 30, 40, 50 and 60 m were obtained using the Brower timing systems (Brower, USA) where the step length and step rate of the distance interval 40-50 of each participant was recorded by a video camera (Sony-HDR SR10E) and calculated using the Peak Motus. Data were analyzed with descriptive statistics (mean, SD) and with t-test in order to examine the differences between the two groups (E & C) and between the pre-post performance tests. The significance level for the tests was set at 0.05 (p < 0.05).